1974
DOI: 10.1001/archpedi.1974.02110230056008
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome: Informing the Parents

Abstract: This study determined the actual experiences of 85 sets of parents when they were informed that their child had Down syndrome, and how they would have preferred this matter to have been handled. The survey revealed that the majority of parents preferred to be told as early as possible with both of them present. They also reported that they found it helpful when the physician provided them with reading materials, recommended they get in touch with other parents with a similar problem, encouraged them to return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 4 publications
7
22
0
Order By: Relevance
“…Egyptian mothers showed preferences similar to The Saudi mothers’ and to those of their counterparts in Western countries; they preferred that BBN be conducted early, in detail, in person, and in a quiet setting [13-18]. Present results are consistent with Gayton and Walker [20] who reported that 90% of parents prefer to be told within the first week.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Egyptian mothers showed preferences similar to The Saudi mothers’ and to those of their counterparts in Western countries; they preferred that BBN be conducted early, in detail, in person, and in a quiet setting [13-18]. Present results are consistent with Gayton and Walker [20] who reported that 90% of parents prefer to be told within the first week.…”
Section: Discussionsupporting
confidence: 85%
“…In 1970, Carr [19] reported that for British families, only 33% were told with both parents present. Studies of American families in the 1970s reported that 20% to 24% of parents were told together [20,21], although 86% would have preferred to be together when told [20]. In our study, mothers were interviewed alone because fathers often were not available.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The first is that parents want to know as soon as possible if something is wrong, even though doctors maybe unsure of the exact nature of the impairment. Most studies lead to the conclusion that delay and uncertainty are likely to cause additional distress for the parents and have a lasting effect on their relationship with doctors (Hewett, Newson &: Newson, 1970;Gayton & Walker, 1974;Carr, 1975Carr, ,1976Pueschel 8c Murphy, 1976;Cunningham 8c Sloper, 1977). Both the National Association for Mental Health (1971) and the Association of Professions for the Mentally Handicapped (APMH) (1981) have drawn up guidelines for telling parents.…”
Section: Discussionmentioning
confidence: 99%